2020
DOI: 10.1038/s41598-020-76601-5
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicular dynamics, progesterone concentrations, pregnancy rates and transcriptional patterns in Bos indicus females with a high or low antral follicle count

Abstract: We evaluated the effect of the antral follicle count (AFC) on ovarian follicular dynamics, pregnancy rates, progesterone concentrations, and transcriptional patterns of genes in Nelore cattle (Bos taurus indicus) after a timed artificial insemination (TAI) programme. Cows were separated based on the AFC, and those with a high AFC showed a larger (P < 0.0001) ovarian diameter and area than those with a very low AFC. Females with a very low AFC exhibited a larger (P < 0.01) diameter of the dominant follicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 62 publications
(101 reference statements)
2
12
1
Order By: Relevance
“…Although the present study did not detect a difference in the P/AI between Low and High AFC heifers, another study performed with Nelore cows observed a negative association between AFC and P/AI (Morotti et al, 2018). In addition, Nelore females with high AFC had lower serum progesterone concentrations after ovulation and lower fertility in TAI programs (Lima et al, 2020). The difference in the cut-off to determine low and high AFC females could be another source of variation in the present study.…”
contrasting
confidence: 79%
See 1 more Smart Citation
“…Although the present study did not detect a difference in the P/AI between Low and High AFC heifers, another study performed with Nelore cows observed a negative association between AFC and P/AI (Morotti et al, 2018). In addition, Nelore females with high AFC had lower serum progesterone concentrations after ovulation and lower fertility in TAI programs (Lima et al, 2020). The difference in the cut-off to determine low and high AFC females could be another source of variation in the present study.…”
contrasting
confidence: 79%
“…Several studies have estimated the relationship between AFC and fertility in B. indicus (Moraes et al, 2019;Morotti et al, 2018;Lima et al, 2020). However, the relationship between AFC, pubertal status, and fertility in heifers has not been deeply investigated.…”
mentioning
confidence: 99%
“…In one such study, in vitro produced embryos from pre‐pubertal cow heifers exhibiting a high response (≥20 follicles) to exogenous gonadotropin stimulation, yielded 100% PRs (Taneja et al., 2000). Without taking into account the wave pattern, a higher follicular count favouring pregnancy has been linked to elevated luteal phase P4 concentration (de Lima et al., 2020; Jimenez‐Krassel et al., 2009), which in turn increased the endometrial thickness, interpreted as a better endometrial development favouring pregnancy (Jimenez‐Krassel et al., 2009). To the contrary, unchanged endometrial thickness in spite of higher P4 concentrations is also on record (Muth‐Spurlock et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…pregnancy has been linked to elevated luteal phase P4 concentration(de Lima et al, 2020;Jimenez-Krassel et al, 2009), which in turn increased the endometrial thickness, interpreted as a better endometrial development favouring pregnancy(Jimenez-Krassel et al, 2009). To the contrary, unchanged endometrial thickness in spite of higher P4 concentrations is also on record(Muth-Spurlock et al, 2017).…”
mentioning
confidence: 99%
“…In contrast, a high conception rate was observed after the use of TAI in low AFC females Bos taurus indicus compared to high AFC animals [43,44]. Additionally, other authors [45] observed that high AFC Bos taurus taurus females had lower fertility and shorter reproductive life than females with low AFC, but contrasting data have been reported [46].…”
Section: Antral Follicle Count and Fertility In Dairy Cattlementioning
confidence: 94%